2015
DOI: 10.1007/s11356-015-5160-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate type on microbial community structure in vertical-flow constructed wetland treating polluted river water

Abstract: Microorganisms attached on the surfaces of substrate materials in constructed wetland play crucial roles in the removal of organic and inorganic pollutants. However, the impact of substrate material on wetland microbial community structure remains unclear. Moreover, little is known about microbial community in constructed wetland purifying polluted surface water. In this study, Illumina high-throughput sequencing was applied to profile the spatial variation of microbial communities in three pilot-scale surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 63 publications
(67 reference statements)
1
33
2
Order By: Relevance
“…In a VF wetland operated under OLR of 27 g COD m -2 d -1 was identified that Nitrosomonas europaea, N. mobilis and Nitrosospira were dominant AOBs in the filter media (Tietz et al, 2007). Guan et al (2015) evaluated in three VF wetlands (1.2 m²) the influence of different substrates (sand, zeolite and gravel) and showed that the bacterial community was significantly influenced by substrate type. However, Nitrospira one of the NOB, was abundant in all units showing no influence of substrate type.…”
Section: Introductionmentioning
confidence: 99%
“…In a VF wetland operated under OLR of 27 g COD m -2 d -1 was identified that Nitrosomonas europaea, N. mobilis and Nitrosospira were dominant AOBs in the filter media (Tietz et al, 2007). Guan et al (2015) evaluated in three VF wetlands (1.2 m²) the influence of different substrates (sand, zeolite and gravel) and showed that the bacterial community was significantly influenced by substrate type. However, Nitrospira one of the NOB, was abundant in all units showing no influence of substrate type.…”
Section: Introductionmentioning
confidence: 99%
“…Proteobacteria was the most dominant phylum in almost all samples, accounting for more than 50% of the total detected reads (except Day1 and SF), followed by Bacteroidetes, Actinobacteria, Verrucomicrobia, Planctomycetes, Patescibacteria and Cyanobacteria. These phyla were also reported as dominant phylum in other CW systems [50,51]. Besides, more than half of the Proteobacteria were from class of Gammaproteobacteria.…”
Section: Microbial Community Structural Changes During Test Operationmentioning
confidence: 69%
“…Proteobacterial microorganisms were commonly found in CW and sand filtration systems [50,[58][59][60] and considered playing important roles in the biodegradation or biotransformation of organic compounds in surface water CW systems or filtration systems [59,61]. Therefore, Proteobacteria might have helped to biodegrade the target PPCP compounds and some microorganisms e.g.…”
Section: Dynamic Otus Changes Of Proteobacteriamentioning
confidence: 99%
“…Microorganisms belonging to the phyla Proteobacteria and Firmicutes are able to degrade a variety of organic compounds, which accounts for the effective removal of DOC [14]. For example, the genera Pseudomonas, Acinetobacter and Bacillus have been linked to the biological degradation of organic and natural compounds [57,58]; however, no significant correlations were observed between these genera and DOC in the LEW, except for the genus Acinetobacter. Wetlands play an important role in methane emissions, and the methanogenic microorganisms involved in this process are also assumed to play vital roles in degrading organic carbon [59].…”
Section: Potential Roles Of the Dominant Bacterial And Archaeal Taxa mentioning
confidence: 99%